2000
DOI: 10.1161/01.str.31.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Atherosclerosis at Middle Age Predicts Cerebral White Matter Lesions in the Elderly

Abstract: Background and Purpose-MRI scans of the brains of elderly people frequently show white matter lesions. Clinically, these lesions are associated with cognitive impairment and dementia. A relation between atherosclerosis and white matter lesions was found in some small cross-sectional studies. However, atherosclerosis is a gradual process that starts early in life. We investigated the longitudinal association between aortic atherosclerosis assessed during midlife and late life and cerebral white matter lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 33 publications
7
64
0
2
Order By: Relevance
“…Indeed, PVH and subcortical or deep white matter lesions (ie, WMH) have been associated with different clinical conditions. 1,43,44 Vascular risk factors were shown to be correlated more strongly with PVH than with WMH, 45 but this is unlikely to be the only explanation for our results, as they remained unchanged after adjustment for vascular risk factors. It has been suggested that lesions affecting the periventricular area may impair cognitive functioning more easily than lesions affecting the subcortical area.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, PVH and subcortical or deep white matter lesions (ie, WMH) have been associated with different clinical conditions. 1,43,44 Vascular risk factors were shown to be correlated more strongly with PVH than with WMH, 45 but this is unlikely to be the only explanation for our results, as they remained unchanged after adjustment for vascular risk factors. It has been suggested that lesions affecting the periventricular area may impair cognitive functioning more easily than lesions affecting the subcortical area.…”
Section: Discussionmentioning
confidence: 58%
“…Because the deep white matter is an arterial border zone already marginally perfused under physiologic circumstances, it is vulnerable to a decrease in cerebral blood flow. 30 Reduced cardiac output in patients with AF may induce ischemia of the deep white matter, causing lesions. 31 We have already reported that an irregular heart rate blunts nitric oxide (NO) synthesis and increases p-selectin expression on platelets, ultimately increasing the risk for silent BI.…”
Section: Discussionmentioning
confidence: 99%
“…A history of cerebrovascular disease (51), the presence of aortic atherosclerosis during midlife (52), and the presence of carotid atherosclerosis (14) were preferentially associated with PVWML. High serum carotenoid level which had been reported to be protective for carotid atherosclerosis was related to decreased PVWMLs but not to DWMLs (53).…”
Section: Etiologic Factorsmentioning
confidence: 99%